DESIGN LKPD TERINTEGRASI INKUIRI TERBIMBING BERBANTUAN VIRTUAL LABORATORY PADA MATERI FLUIDA DINAMIS DAN TEORI KINETIK GAS DALAM PEMBELAJARAN FISIKA KELAS XI SMA - Nira Aslinda; Hufri Hufri; Harman Amir (Universitas Negeri Padang, 2017)
This research is motivated that teaching materials in schools have not facilitated students optimally in finding their knowledge. In addition, practicum activities are also not always done in Physics learning, due to the limitations of practicum tools. So that learning is still centered on the teacher and make learners less active and just memorize the formula instead of understanding the concept. This study aims to produce products in the form of RPP and LKPD integrated inquiry guided with virtual laboratory on the material Dynamic Fluid and Gas Kinetic Theory in a valid, practical and effective physics learning. This research was a research development (research and development) using 4D development model. This model consists of 4 stages of define, design,, development and disseminate. However, this study was only done until the stage of development. The data of the research was analyzed by qualitative and quantitative analysis. This research produces products in the form of integrated RPP and LKPD guided inquiry with virtual laboratory assisted. Based on the data analysis can be presented three research results. First, the validity of RPP and LKPD that validated the experts each have an average value of 91.46 and 89.84 with criteria is very valid. Second, the practicality of teachers for RPP is 93.31% and for LKPD is 95.31% and practicality value of learners that is 89.67% who are on very practical criteria. Third, integrated LKPD guided inquiry with virtual laboratory is effectively used in physics learning